Mapping Rhizoctonia root and crown rot resistance from sugar beet germplasm FC709-2 using new genomic resources - Metz, Nicholas, author; Mason, Esten, advisor; Dorn, Kevin, committee member; Richards, Christopher, committee member; Gaines, Todd, committee member (Colorado State University. Libraries, 2024)
Sugar beet (Beta vulgaris subsp. Vulgaris) provides about 35% of the refined sugar globally, and over half of the domestic production in the United States. Sugar beet are primarily grown in temperate climates from plantings in late spring and harvest in the fall. In the United States sugar beets are grown in four diverse regions: the upper Midwest (Minnesota and North Dakota), the far west (California, Idaho, Oregon, and Washington, the Great Plains (Colorado, Nebraska, Montana, and Wyoming), and the Great Lakes (Michigan). Multiple pests and pathogens continue to threaten tonnage and recoverable sugar yields. These are controlled through planting genetically resistant cultivars, agronomic cultural practices and chemical applications throughout the growing season. With a shrinking set of chemical and cultural control options to manage these production threats, the need for continued improvement upon host plant resistance is important. Decades of global breeding efforts to improved disease tolerance in sugar beet has been effective, but molecular and genomic guided breeding and disease resistance characterization in sugar beet is only now emerging. The most important root pathogen in sugar beet is Rhizoctonia Root and Crown Rot (RRCR) caused by the fungal pathogen Rhizoctonia solani. This disease is estimated to cause up to 50% localized losses, and regularly causes 57 million dollars in economic losses per year despite the use of tolerant varieties, chemical control, and cultural practices. Public sugar beet pre-breeding has developed hundreds of widely utilized lines with novel traits and combinations of traits, including for RRCR resistance. One such line, FC709-2, displayed exceptional tolerance to Rhizoctonia solani released from the United States Department of Agriculture sugar beet breeding program in Fort Collins, Colorado. This germplasm line is base for many RRCR resistant cultivars used by growers around the world. In this study, new germplasm, genetic, and genomic resources revolving around FC709-2 were developed. These resources include a new germplasm line derived from the purification of FC709-2. By using stricter selection pressure and single seed decent a more homogenous seed lot was created to be used by other breeding programs. A new reference genome created from a single highly RRCR resistant plant using the most recent sequencings and bioinformatic technologies will be used to discover genes that are responsible for a wide array of plant interactions. Last, novel QTLs associated with RRCR resistance were discovered using a bi-parental mapping population and bulk segregate analysis. Collectively, these results show that discovering novel RRCR resistance genes in a highly resistant germplasm line using a purpose-built reference genome is a streamlined and accurate method. With these new resources in place researchers around the world can use them to discover the genes responsible for RRCR resistance, create markers for more accurate selections, and follow the methods described to be implemented in other plant breeding programs.
Keywords: genome; sugarbeet; genomics; genetics